Bioinformatics Tools In Clinical Microbiology and Infectious Disease Prevention Algorithms - Kim, Hyunjo (Journal of Medical Biomedical and Applied Sciences, 2018)
Bioinformatics resource is the exploitation of genome sequence data for diagnostic, therapeutic, and preventionpurposes. The role of clinical genomics in infectious disease is aimed at describing the structure of outbreakcommunities, the methodology works equally well to identify pathogens in clinical samples. Furthermore, early detectionof infectious disease in outbreaks is one of the significant issues in syndromic surveillance systems. The key concept inusing clinical genomics methodology is a process of generating large-scale sequence data sets that adequately samplea specimen for microbial content and then of applying computational methods to resolve the sequences into individualspecies, genes, pathways, or other features. It helps to provide a rapid epidemiological response and reduce morbidityand mortality. Therefore, bioinformatics model algorithms for virus transmission and prevention in terms of resistomewould be taken into consideration. The relevant future study of resistome reveals strategies that can be applied in newantibiotic discoveries.